Is metabolic syndrome a risk factor in hepatectomy?: A meta-analysis with subgroup analysis for histologically confirmed hepatic manifestations - Murtha-Lemekhova, Anastasia; Fuchs, Juri; Feiler, Svenja; Schulz, Erik R.; Teroerde, Miriam; Kalkum, Eva; Klotz, Rosa; Billeter, Adrian; Probst, Pascal; Hoffmann, Katrin (BMC medicine, 2022)
Metabolic syndrome (MetS) is a risk factor in surgery. MetS can progress to metabolic (dysfunction)-associated fatty liver disease (MAFLD), a vast-growing etiology of primary liver tumors which are major indications for liver surgery. The aim of this meta-analysis was to investigate the impact of MetS on complications and long-term outcomes after hepatectomy.